BUDAYA SPIRITUAL DI SEKITAR KAWASAN PT. HUTAN KETAPANG INDUSTRI KECAMATAN KENDAWANGAN KABUPATEN KETAPANG (Studi Kasus Desa Pangkalan Batu, Desa Kedondong dan Desa Mekar Utama) - Asmaiah, Asmaiah; Rifanjani, Slamet; Muflihati, Muflihati (Universitas Tanjungpura, 2024)
Spiritual culture is a manifestation of inner culture that can only be communicated through the expression of symbols that are still alive. This culture can be understood and has become a belief of the Dayak people that cannot be changed. The forms of spiritual culture include customs, language, tools, clothing, buildings, and works of art that develop and are passed down from generation to generation. PT Hutan Ketapang Industri is an industrial plantation forest company that helps protect spiritual culture and important locations for traditions/customs in order to maintain the cultural identity of local residents. The purpose of the study was to obtain and analyze data on spiritual culture around PT Hutan Ketapang Industri in kendawangan sub-district, Ketapang Regency. This study uses a survey method. Data collection by interview using the snowball sampling technique. Interviews were conducted with the Village Headwho was the key respondent to obtain information about spiritual culture with a question guide. Data analysis techniques using descriptive methods with a qualitative approach. The results of spiritual culture research show cultural sites, traditional rituals and objects used in traditional rituals. Spiritual culture is still maintained and preserved today by the people of Pangkalan Batu Village, Kedondong Village and Mekar Utama Village. Keywords: Key Responden, PT. Hutan Ketapang Industri, Snowball, Spiritual Culture Abstrak Budaya spiritual merupakan perwujudan budaya batin yang hanya dapat dikomunikasikan melalui eksperesi simbol-simbol yang masih hidup. Budaya ini dapat dipahami dan sudah menjadi kepercayaan masyarakat dayak yang tidak dapat diubah. Bentuk budaya spiritual tersebut antara lain adat istiadat, bahasa, perkakas, pakaian, bangunan, dan karya seni yang berkembang dan diwariskan dari generasi ke generasi. PT. Hutan Ketapang Industri merupakan perusahaan hutan tanaman industri yang ikut melindungi budaya spiritual serta lokasi penting bagi tradisi/adat agar terjaganya identitas budaya warga setempat. Tujuan penelitian untuk memperoleh dan menganalisis data budaya spiritual di sekitar PT. Hutan Ketapang Industri Kecamatan kendawangan Kabupaten Ketapang. Penelitian ini menggunakan metode survey. Pengumpulan data dengan wawancara menggunakan teknik snowball sampling. Wawancara dilakukan kepada Kepala Desa yang merupakan responden kunci untuk mendapakan informasi tentang budaya spiritual dengan panduan pedoman pertanyaan. Teknik analisis data menggunakan metode deskriptif dengan pendekatan kualitatif. Hasil penelitian budaya spiritual menunjukkan situs budaya, ritual adat dan benda-benda yang digunakan dalam ritual adat. Budaya spiritual masih dijaga dan dilestarikan hingga sampai sekarang oleh masyarakat Desa Pangkalan Batu, Desa Kedondong dan Desa Mekar Utama. Kata kunci: Responden Kunci, PT. Hutan Ketapang Industri, Snowball, Budaya Spiritual